Distribution of water in ceramic green bodies during drying. Issue 10 (August 2019) - OUMMADI, Siham; Nait-Ali, Benoit; Alzina, Arnaud; Victor, Jean-Louis; Launay, Yann; Mirdrikvand, Mojtaba; Dreher, Wolfgang; Rezwan, Kurosch; Smith, David S.
Abstract: In order to investigate drying mechanisms at different stages, the distribution of water within the ceramic green bodies at different scales has been examined. The experimental measurements, using a simple weighing technique and Magnetic Resonance Imaging (MRI), show that during the first stage of drying involving shrinkage the material is constituted of uniquely solid and water with no gradient in water content within the sample. Then, during the second stage of drying, significant differences of water content as a function of position appear. As a complement, at the grain scale, observations using environmental scanning electron microscopy were made giving useful information on the solid–liquid–gas interfaces in the near surface part of the green body. Finally, the gradients in the water distribution were exploited to make a simple estimate of the diffusion coefficient of water with its dependence on the moisture content.